Evaluation of outcome in laparoscopic and open ventral hernia repair: a prospective study - Aggarwal, Shubhankar; Sachan, P. K.; Mittal, Vinamra (International Surgery Journal, 2022)
Background: Ventral hernias are categorized as epigastric, umbilical, spigelian, parastomal, and incisional hernias. Hernias occurring in epigastrium and umbilical region are considered as primary ventral hernias. There are various ways of hernia repair, in which the tension free repair remains the most important one. For doing a repair by laparoscopy, first of all the contents of the hernia are reposited back in the abdomen, followed by placement of mesh transabdominally which should be of optimum size and type Methods: The present study is a prospective observational study that emphasizes to analyse and evaluate outcome in open and laparoscopic mesh repair of ventral hernia that presented to the Himalayan hospital over a period of 1 year. Results: Study shows that more than 50% of the cases were recorded in the age group between 26-50 years (mean 47 years) with majority being females. Umbilical hernia (45.1%) was the most common followed by incisional hernia (28.2%), paraumbilical hernia (22.5%) and epigastric hernia (4.2%). Diabetes mellitus was the most common comorbidity (88.7%) followed by hypertension (64.8%). VAS score was statistically significant between individuals who got surgery by laparoscopy when compared with open approach. A significant difference was also observed between period of mobilization and surgical procedure. Conclusions: Surgery of ventral hernia by laparoscopy has less post-surgical pain, less problems, lesser stay in hospital and had lesser impact on economy as the individuals returned to their normal routine in lesser time.